ASSESSMENT OF ALLEXIVIRUSES INFECTION IN GARLIC PLANTS IN POLAND - Maria Chorodorska; Elżbieta Paduch-Cichal; Elżbieta Kalinowska; Marek Stefan Szyndel (Acta Scientiarum Polonorum: Hortorum Cultus, 2014)
Garlic (Allium sativum L.) plants may be infected in the field by viruses of the genera Potyvirus, Carlavirus and Allexivirus. These viruses are transmitted by vegetative propagation and by vectors. Detection and identification of allexiviruses was carried out in 2011–2012. It was based on ELISA and RT-PCR assays. Samples of plant material were collected from 26 garlic production fields located in different regions of Poland. Garlic virus D, Garlic virus B and Garlic virus X were the most abundant viruses in all examined regions and were identified in 79%, 64% and 59% of all garlic samples, respectively. Garlic virus A and Garlic virus C were identified in all studied regions with low frequency. Garlic virus E was detected with 100% frequency in east-central Poland. None of the tested garlic samples were infected with Shallot virus X. Allexiviruses were always present in garlic plants in mixed infections.